2018
DOI: 10.1016/j.isci.2018.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Snakeskin Limits Microbial Dysbiosis during Aging and Promotes Longevity

Abstract: SummaryIntestinal barrier dysfunction is an evolutionarily conserved hallmark of aging, which has been linked to microbial dysbiosis, altered expression of occluding junction proteins, and impending mortality. However, the interplay between intestinal junction proteins, age-onset dysbiosis, and lifespan determination remains unclear. Here, we show that altered expression of Snakeskin (Ssk), a septate junction-specific protein, can modulate intestinal homeostasis, microbial dynamics, immune activity, and lifesp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
110
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(118 citation statements)
references
References 48 publications
7
110
1
Order By: Relevance
“…Our experiments show that tumor growth impairs the intestinal renewal capacity and barrier function by inducing gut integrity loss, immune activation, reduced Duox expression and in turn causes intestinal dysbiosis. This is consistent with previous results showing that intestinal barrier failure after loss of a septate junction protein Snakeskin results in altered gut morphology, dysbiosis and reduced Duox level (Salazar et al, 2018). Duox act as an important defence mechanism in ECs against enteric infection and its expression is increased in the intestine during infection and ageing (Lee et al, 2018;Guo et al, 2014), suggesting that Duox expression is induced during normal intestinal regeneration under infection or ageing, while its expression is dampened in the tumor bearing intestine with massive loss of ECs and impaired EC renewal capacity.…”
Section: Tumor Growth Causes Intestinal Dysfunction and Dysbiosissupporting
confidence: 93%
See 2 more Smart Citations
“…Our experiments show that tumor growth impairs the intestinal renewal capacity and barrier function by inducing gut integrity loss, immune activation, reduced Duox expression and in turn causes intestinal dysbiosis. This is consistent with previous results showing that intestinal barrier failure after loss of a septate junction protein Snakeskin results in altered gut morphology, dysbiosis and reduced Duox level (Salazar et al, 2018). Duox act as an important defence mechanism in ECs against enteric infection and its expression is increased in the intestine during infection and ageing (Lee et al, 2018;Guo et al, 2014), suggesting that Duox expression is induced during normal intestinal regeneration under infection or ageing, while its expression is dampened in the tumor bearing intestine with massive loss of ECs and impaired EC renewal capacity.…”
Section: Tumor Growth Causes Intestinal Dysfunction and Dysbiosissupporting
confidence: 93%
“…2C). Since the comparative analysis did not provide information about the extent changes in taxa abundance and changes in the overall microbiome (Vandeputte et al, 2017), we examined the load of various bacteria by CFU assays on selective mediums for Acetobacteriaceae and other bacteria (NR) (Ryu et al, 2008;Guo et al, 2014) as well as by taxa-specific 16S qPCR (Clark et al, 2015;Salazar et al, 2018). In these experiments, we observed intestinal dysbiosis in Dpp/BMP knock-down conditions (Mad/Med, Shn RNAi), as shown in Fig.…”
Section: Intestinal Tumors Influence the Microbiotamentioning
confidence: 97%
See 1 more Smart Citation
“…During the preparation of our manuscript, two groups published interesting phenotypes of the sSJ-protein-deficient adult midgut in Drosophila that are highly related to the present study. Salazar et al (2018) reported that reduced expression of ssk in ECs leads to gut barrier dysfunction, altered gut morphology, increased stem cell proliferation, dysbiosis, and reduced lifespan. They also showed that up-regulation of Ssk in the midgut protects flies against microbial translocation, limits dysbiosis, and prolongs lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to vertebrates, disruption of septate junctions affects both health and longevity. For example, loss of Ssk affects composition of the gut bacterial community, and upregulation of Ssk extends lifespan (Salazar et al 2018).…”
Section: Discussionmentioning
confidence: 99%